2023
DOI: 10.14198/jhse.2023.182.13
|View full text |Cite
|
Sign up to set email alerts
|

The home-court advantage in NCAA Division-I men’s basketball

Abstract: The purpose of the present study was to examine the differences in game-related statistics between home and away games at the NCAA Division-I level of men's basketball competition. The data scraping technique was used to obtain publicly available box scores during the 2018-19 competitive season. Throughout this period, 2181 home and 2205 away box scores were randomly selected across 353 teams, regardless of the winning or losing game outcome. The findings of the present study revealed that the game-related sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Research indicates that shooting efficiency is a crucial factor in determining game outcomes [41][42][43][44][45][46][47]. Shooting accuracy is an important aspect of basketball performance since it measures both individual and collective offensive efficiency [48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that shooting efficiency is a crucial factor in determining game outcomes [41][42][43][44][45][46][47]. Shooting accuracy is an important aspect of basketball performance since it measures both individual and collective offensive efficiency [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, points scored on two-pointers imply poor defense by the losing team's interior players (centers) [60]. Studies on game-related statistics in women's basketball have proven the continued relevance of two-point field goals [43,55]. Research on women's national team tournaments has also indicated that winning teams score more points in the paint, points off opponent turnovers (fast breaks), and second-chance points following successful offensive rebounds [29].…”
Section: Discussionmentioning
confidence: 99%
“…Data scraping technique was used to obtain publicly available game-related statistics for NCAA Division-I men's basketball 2018–2019 competitive season from https://stats.ncaa.org website (i.e., contest - scoreboard - box score) via ParseHub software (North York, ON, Canada). This research report represents a follow-up analysis based on a previously published manuscript focused on examining the impact of home-court advantage on the same level of competition ( 14 ). The following 18 variables (i.e., team averages) were acquired from the box scores across 5,147 games: field goals made (FGM), field goals attempted (FGA), field goal shooting percentage (FG%), 3-point shots made (3PM), 3-point shots attempted (3PA), 3-point shooting percentage (3P%), free-throws made (FTM), free-throws attempted (FTA), free-throw shooting percentage (FT%), offensive rebounds (ORB), defensive rebounds (DRB), total rebounds (TBR), assists (AS), steals (ST), blocks (BL), turnovers (TO), personal fouls (PF), and points (PTS).…”
Section: Methodsmentioning
confidence: 99%
“…Shooting efficiency has been shown to be one of the key performance parameters differentiating winning from losing game outcomes in basketball, ranging from amateur to professional levels of competition [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. In a recently published study examining game-related statistics within a cohort of elite women’s basketball players, Madarme [ 8 ] found that successful two-point field goals discriminated winning from losing teams during balanced games played on Under-19 level of competition (i.e., a final score differential <16 points).…”
Section: Introductionmentioning
confidence: 99%